Legal consequences from unilateral deduction of employees’ wages or salary - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bad, 2018)
The contract law which is the product of the industrial revolution and the doctrine of laissez-faire as its justification applies to a contract of employment. A contract may be created without formal documents or even an express agreement, be it in written form or orally made. It can also arise from non-verbal agreements such as conduct. For a contract to bind the parties, they must intend to create a legally binding obligation. One of the significant or fundamental terms of the employment contract is the payment of wages or salaries.1 It must be paid promptly and within the period specified by the law or as agreed to by the parties. Further, any deduction from the employee’s wages or salary must be done with the consent of the employee. The implications ensuing from a unilateral deduction of an employee’s salary or wages forms the discussion of this article with reference to the awards of the Industrial Court.